2011
DOI: 10.1371/journal.pone.0024252
|View full text |Cite
|
Sign up to set email alerts
|

IFN-α Is Constitutively Expressed in the Human Thymus, but Not in Peripheral Lymphoid Organs

Abstract: Type I interferons have been typically studied for their effects in the context of bacterial or viral infections. However in this report, we provide evidence that Interferon-alpha (IFN-α) expressing cells are present in the thymus in the absence of infection. We show that pDC express the highest level of IFN-α and that MxA, which is exclusively expressed after engagement of the type I IFN receptor by IFN-α/β, is expressed in normal fetal and post-natal thymus, but not in the periphery. The highest level of MxA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…Indeed, factors such as TGFβ, Wnt, and type I interferons can all modify the maximum amplitude of Notch signaling through various ways (64) (Amsen, unpublished data). TECs produce TGFβ (71), while thymic plasmacytoid DCs constitutively express IFNα under non-inflamed conditions (72), indicating once more that both epithelial and non-epithelial stromal components of the thymic microenvironment might contribute to specialized niches capable of eliciting strong Notch signals in developing thymocytes. Given that mice lacking thymic epithelial cells still generate ILC2 (23), it is tempting to speculate that the relevant source of the Notch activating signals consists of a non-epithelial stromal cell.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, factors such as TGFβ, Wnt, and type I interferons can all modify the maximum amplitude of Notch signaling through various ways (64) (Amsen, unpublished data). TECs produce TGFβ (71), while thymic plasmacytoid DCs constitutively express IFNα under non-inflamed conditions (72), indicating once more that both epithelial and non-epithelial stromal components of the thymic microenvironment might contribute to specialized niches capable of eliciting strong Notch signals in developing thymocytes. Given that mice lacking thymic epithelial cells still generate ILC2 (23), it is tempting to speculate that the relevant source of the Notch activating signals consists of a non-epithelial stromal cell.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the innate immune system by poly(I:C) injection causes rapid ATI that is mediated by the virus-sensing melanoma differentiationassociated gene 5 receptor, and the type 1 IFN receptor significantly impacts this process (Anz et al 2009). Although IFN-α is constitutively present in the human thymus (Colantonio et al 2011) and acts as a key regulator of pathogeninduced ATI, microRNA miR-29a has also been found to play a critical role in the protection of thymus from involution. For instance, selective deletion of microRNA miR29a from the TECs leads to increased expression of the IFN-α receptor, which results in a loss of cellularity in the thymus and thus causes the ATI (Fig.…”
Section: Role Of Microrna and Ifn-α Receptors In Viral Infection Medimentioning
confidence: 99%
“…Previously, we have shown that human thymic pDCs are the likely source of the constitutive production of IFN‐α in the thymus as a result of TLR‐induced activation . Here we aimed at extending our findings.…”
Section: Resultsmentioning
confidence: 56%
“…1. We have previously shown that the amount of IFN‐α produced by thymic pDCs constitutively, or after stimulation with CpG or HIV, greatly varies between donors . Further, as shown in Fig.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation